2021
DOI: 10.1111/1467-8500.12473
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine co‐design and value co‐creation in public health care

Abstract: COVID‐19 has presented significant challenges for public healthcare systems across the globe. The critical challenge for public healthcare organisations is to provide effective health care to patients, while simultaneously keeping frontline staff safe. Telemedicine has emerged as a prominent service intervention to this end. Telemedicine integrates technologies into medical practices to alleviate the need for face‐to‐face interactions through video consultations. The study explores how physicians and patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…This service integrates the use of technology into medical practices to reduce face-to-face meetings. Leite and Hodgkinson [25] built a framework to examine how patients and doctors can co-create service value for the telemedicine ecosystem with/for any kind of crisis. They collected a sample about telemedicine and included 146 tweets from patients and 734 tweets from doctors.…”
Section: Social Media and Healthcarementioning
confidence: 99%
“…This service integrates the use of technology into medical practices to reduce face-to-face meetings. Leite and Hodgkinson [25] built a framework to examine how patients and doctors can co-create service value for the telemedicine ecosystem with/for any kind of crisis. They collected a sample about telemedicine and included 146 tweets from patients and 734 tweets from doctors.…”
Section: Social Media and Healthcarementioning
confidence: 99%
“…Thus, UI strategy for new product and service development is applied differently in this special setting and a critical and insightful question is who the users participating in UI are in e-health innovations. The results of coding the users involved in the 169 sample publications show that they fall into one of the following seven categories:Patients or persons related to a specific disease in different stages such as under-treatment patients, cured patients, screened patients or patients in remedy (Leite and Hodgkinson, 2021; Schmidt et al. , 2021; Quintana et al.…”
Section: Resultsmentioning
confidence: 99%
“…(1) Patients or persons related to a specific disease in different stages such as undertreatment patients, cured patients, screened patients or patients in remedy (Leite and Hodgkinson, 2021;Schmidt et al, 2021;Quintana et al, 2020).…”
Section: Content Analysismentioning
confidence: 99%
“…The present paper has contributed to the development of the public service logic by recognizing how turbulent times, such as the COVID-19 pandemic, may accelerate reforms in a desired direction, even reforms that have been stationary for quite some time. However, the paper has also highlighted that expected enablers for value co-creation in these service ecosystems, such as telemedicine (Leite and Hodgkinson (2021), may be underused, despite the sense of urgency.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that mainly traditional telephone calls were used rather than digital communication applications, even though digital services were mentioned as important for people to access public services (Dunleavy et al, 2006;Melchiorre, 2018) as well as in the interviews before the pandemic. Leite and Hodgkinson (2021) found that telemedicine, or face-to-face video consultations, may be a way for patients and healthcare staff to co-create the service in a public service fashion during the pandemic. Moreover, the inclusion of the citizens' and patients' perspectives would have led to new and innovative ways of carrying out healthcare services during pandemic (Eriksson, 2019).…”
Section: A Delimited Ecosystemmentioning
confidence: 99%